Dynamic matter : transforming Renaissance objects - Wood, Jennifer Linhart (Cultural inquiries in English literature, 1400-1700., 2022)
"Investigates the life histories of Renaissance objects as they experience transformations, and demonstrates these objects' dynamic potential to transform their environments and others as they journey through time and space"--